Gasification of torrefied cassava rhizome with Ni/MCM-41 catalyst derived from illite waste. (November 2020) - Sirinwaranon, Punchaluck; Atong, Duangduen; Sricharoenchaikul, Viboon
Abstract: In this work, torrefaction of cassava rhizome (CR) under nitrogen gas ( N 2 ) and a simulated flue gas (CO2 (15 vol.%) and O 2 (5 vol.%) in N 2 balance) atmosphere was examined in a downflow reactor at 260ºC for a residence time of 60 min to produce a superior solid fuel for subsequent 5Ni/MCM-41 catalytic gasification of CR utilization. Mesoporous molecular sieves (MCM-41 zeolite) was synthesized from illite waste as a silica source. The MCM-41 synthesis was carried out by hydrothermal and post-synthesis for Ni loading. Various characterization techniques, such as XRD, SEM, and BET were employed to thoroughly characterize catalyst. High surface area (737.88 m 2 /g) and a typical type IV pattern of hysteresis loop (0.25 –0.40) obtained 5Ni/MCM-41 catalyst is calculated by N 2 adsorption–desorption technique. Catalyst characterization and discussion of results are presented in this work. 5Ni/MCM-41 catalyst strongly enhances the H 2 and CO production from gasification of torrefied CR at a temperature of 700ºC. Carbon and hydrogen conversions were 80.17% and 27.39%, respectively while liquid yield was lower than 10 wt%. The syngas from the conversion maintained H 2 /CO ratio of 0.55 with the highest gaseous efficiency of 49.35%. Obviously, synergy of synthesized 5Ni/MCM-41 catalyst and torrefied CR with gasification is valuable useful as potential renewable energy generation process.